A humidity-responsive CO2 separation material and its preparation and application
By solvent modification and functional group loading of cellulose, a humidity-responsive CO2 separation material was prepared, which solved the problems of low CO2 capture capacity and narrow application range in the prior art, and achieved efficient CO2 in high humidity environments Capture and wide application scope.
Patent Information
- Application Number
- CN202411606610.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The CO2 trap capacity of the existing humidity-responsive adsorbent is relatively low and has a narrow range of application. Especially in high humidity environments, the CO2 trap capacity decreases, making it difficult to take into account both high capture capacity and wide application range.
By dispersing cellulose in a good solvent to destroy hydrogen bonds, then cross-linking and modifying with tertiary amine polymers and quaternary ammonium salt compounds, and ion exchange in a strong alkali and weak acid solution, a tertiary amine group is prepared. , humidity-responsive CO2 separation material of quaternary ammonium salt group and imidazolium salt group.
It realizes efficient adsorption of CO2 in the air, and maintains a high capture capacity and adsorption rate within the humidity range of 30% to 60%, significantly improving the humidity response sensitivity.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of separating CO2 from air, and in particular to a humidity responsive CO2 separation material and its preparation and application. Background Art
[0002] Direct air carbon capture technology (DAC) can achieve net negative CO2 emissions because it can directly capture excess CO2 from the atmosphere. At the same time, direct air carbon capture technology (DAC) can separate the captured CO2 from the air and utilize it to form a closed carbon cycle, which is expected to achieve the goal of net zero CO2 emissions.
[0003] Humidity-responsive adsorbents have attracted the attention of researchers as a new type of CO2 separation material. This type of material uses the property that the reaction equilibrium between certain adsorbents and CO2 can be adjusted by the partial pressure of ambient water vapor to construct an "adsorption-desorption-regeneration" cycle to achieve efficient separation of CO2. Its uniqueness lies in that the desorption of CO2 and the regeneration of the material are driven by the evaporation of water at the gas-solid interface between air and the adsorbent, and do not rely on high-grade heat sources, so it has the potential to significantly reduce energy consumption and operating costs. However, in related technologies, the CO2 capture capacity of humidity-responsive adsorbents is relatively low (usually less than 1 mmol / g), and most of them are only applicable to dry or low-humidity (relative humidity RH < 30%) air environments, with a narrow scope of application. When RH ≥ 30%, there is often a problem of decreased CO2 capture capacity; high humidity response and large-capacity CO2 capture are difficult to achieve at the same time.
[0004] Therefore, it is necessary to provide a humidity-responsive adsorbent with high CO2 capture capacity and a wide humidity adaptability range to improve the effect of separating CO2 from the air. Summary of the invention
[0005] In view of the defects in the prior art, the present invention proposes a humidity-responsive CO2 separation material and its preparation and application, so as to solve the problem of how to improve the CO2 capture capacity and humidity adaptability range.
[0006] In a first aspect, the present application provides a method for preparing a humidity-responsive CO2 separation material, comprising the following steps:
[0007] S1. dispersing cellulose in a good solvent system to break hydrogen bonds, thereby obtaining uniformly dispersed cellulose with abundant hydroxyl active sites;
[0008] S2. The tertiary amine polymer solution is added dropwise to the cellulose solution, a crosslinking agent is added to perform a Williamson etherification reaction, and then an aqueous solution of a quaternary ammonium salt compound is added to stir the reaction, and then heat treated and rinsed to obtain modified cellulose;
[0009] S3. The modified cellulose is immersed in a solution of a strong base and a weak acid salt to perform ion exchange, and then rinsed with alcohol and dried to obtain a humidity-responsive CO2 separation material; the strong base and weak acid salt contains a trivalent anion.
[0010] Preferably, the good solvent includes one or more of imidazolium chloride ionic liquid and sodium hydroxide / urea mixed solution; the cellulose is type I cellulose, which has a double-chain alternating structure and a crystal density of (1.59-1.61) g·cm -3 , the viscosity average molecular weight is (10-20)×10 4 .
[0011] Preferably, the tertiary amine polymer includes one or more of polyvinyl imidazole and polyvinyl pyridine.
[0012] Preferably, the quaternary ammonium salt compound includes one or more of 3-chloro-2-hydroxypropylammonium chloride, (3-chloro-2-hydroxypropyl)dodecyldimethylammonium chloride, and 2,3-epoxypropyltrimethylammonium chloride.
[0013] Preferably, the strong base weak acid salt includes one or more of sodium phosphate, sodium dihydrogen phosphate, sodium silicate, and sodium borate.
[0014] Preferably, in step S2, the heat treatment temperature is 40-80°C.
[0015] Preferably, the cross-linking agent includes one or more of epichlorohydrin, epibromohydrin, ethylene dichloride and ethylene dibromide.
[0016] Preferably, the mass ratio of cellulose to tertiary amine polymer is 1: (0.5-1.5).
[0017] In a second aspect, the present application provides a humidity-responsive CO2 separation material, which includes cellulose and a tertiary amine group, a quaternary ammonium salt group and an imidazolium salt group loaded on the cellulose.
[0018] In a third aspect, the present application provides an application of a humidity-responsive CO2 separation material in separating CO2 from air, wherein the air humidity is 30%≤≤60%.
[0019] In summary, compared with the prior art, the present invention has achieved the following technical effects: This application uses renewable cellulose as a raw material carrier, optimizes the structural design, and regulates the physical structure and surface chemical properties of the carrier, thereby achieving efficient adsorption of CO2 in the air and improving the sensing sensitivity to humidity (≤60%). DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0021] In a first aspect, the present application provides a method for preparing a humidity-responsive CO2 separation material, comprising the following steps:
[0022] S1. dispersing cellulose in a good solvent system to break hydrogen bonds, thereby obtaining uniformly dispersed cellulose with abundant hydroxyl active sites;
[0023] S2. Using a tertiary amine polymer and a quaternary ammonium salt compound as raw materials, cross-linking and modifying cellulose to obtain modified cellulose;
[0024] S3. The modified cellulose is immersed in a strong base and weak acid salt solution to carry out ion exchange, and then rinsed with alcohol and dried to obtain a humidity-responsive CO2 separation material.
[0025] The present application uses renewable cellulose (such as microcrystalline cellulose, short cotton linters) as a raw material carrier, and optimizes the structural design to regulate the physical structure and surface chemical properties of the carrier, thereby achieving efficient adsorption of CO2 in the air and improving the sensitivity to humidity (≤60%). First, cellulose is dispersed in a solvent to destroy the intramolecular hydrogen bonds and crystalline structure of cellulose, so that it exposes more active hydroxyl sites; secondly, cellulose is in situ modified, and tertiary amine polymers and quaternary ammonium salt functional groups are chemically grafted onto the cellulose structure network to obtain a cellulose gel material with a double network structure. The hydroxyl groups participate in the cross-linking reaction of cellulose and tertiary amine polymers as active sites, and after the tertiary amine polymer of the present application is loaded on the modified cellulose, part of the tertiary amine groups become imidazolium salts, and then the quaternary ammonium salt groups are loaded; then, the anions of strong base and weak acid salts, such as phosphate, borate, silicate, and other multivalent anions are combined with tertiary amine salt / imidazolium / quaternary ammonium salt cations through ion exchange to obtain an adsorbent precursor, and finally, the humidity-responsive CO2 separation material is obtained through solvent exchange and drying.
[0026] The humidity-responsive CO2 separation material obtained in the present application includes cellulose and tertiary amine groups, quaternary ammonium salt groups and imidazolium salt groups loaded on the cellulose, and the three groups jointly act as CO2 adsorption sites, and the adsorption sites are numerous and synergistic with each other; the mechanism by which quaternary ammonium salt compounds, imidazolium salts and tertiary amine groups synergistically improve the CO2 adsorption amount and humidity sensitivity is that: since hygroscopic adsorption mainly depends on the contact between anions and water, the alkaline ions formed after hydrolysis react with CO2, in the present application, the quaternary ammonium salt has small steric hindrance, so that the anions have a faster hydrolysis rate and a faster CO2 adsorption rate; the imidazolium salt has good CO2 adsorption selectivity, and after combining with anions, it has a stronger ability to capture CO2 and a high adsorption selectivity; the tertiary amine group can combine with CO2 in the presence of water, avoiding the problem of decreased CO2 adsorption capacity under high humidity conditions.
[0027] Furthermore, the three groups jointly act as CO2 adsorption sites, which is beneficial to improving the dispersion of the material, thereby improving the adsorption efficiency of the material and further improving the humidity response sensitivity; at the same time, the introduction of imidazolium salts and quaternary ammonium salts enables cellulose to form a double cross-linked network structure, which can form a denser and more stable network structure inside the material, forming an overall adsorbent rather than a cellulose gel product modified by a single group, thereby improving the strength and toughness of the material and avoiding powdering during use.
[0028] In order to further improve the humidity response sensitivity of the material, this application uses strong base and weak acid salt for ion exchange (halogen ions and anions). The anions of this application are high-valent (trivalent) anions, which have a faster hydrolysis rate than carbonate and can combine with CO2 faster, thereby increasing the adsorption rate and improving the humidity response sensitivity.
[0029] In some embodiments, the good solvent includes one or more of imidazolium chloride ionic liquid and sodium hydroxide / urea mixed solution; the cellulose is type I cellulose, which has a double-chain alternating structure and a crystal density of (1.59-1.61) g·cm -3 , the viscosity average molecular weight is (10-20)×10 4 .
[0030] The solvent of the present application destroys the crystalline structure of cellulose and the intramolecular / intermolecular hydrogen bonding, exposing the hydroxyl sites, which is helpful for subsequent modification reactions and is used to better expose the active hydroxyl sites of cellulose. If it is not modified by solvent, the subsequent modification efficiency is low and the reaction conditions are harsh.
[0031] In some embodiments, the tertiary amine polymer includes one or more of polyvinyl imidazole and polyvinyl pyridine.
[0032] The tertiary amine polymer of the present application is a soluble nitrogen-containing organic polymer, which contains only tertiary amine groups and can undergo nucleophilic substitution reaction with halogenated alkanes, and the tertiary amine groups are partially converted into imidazolium salts; the solvent for dissolving the tertiary amine polymer of the present application includes one or more of urea, thiourea, and methyl urea.
[0033] In some embodiments, the quaternary ammonium salt compound includes one or more of 3-chloro-2-hydroxypropylammonium chloride, (3-chloro-2-hydroxypropyl)dodecyldimethylammonium chloride, and 2,3-epoxypropyltrimethylammonium chloride.
[0034] In some embodiments, the strong base weak acid salt includes one or more of sodium phosphate, sodium dihydrogen phosphate, sodium silicate, and sodium borate.
[0035] The anions of the strong base and weak acid salt of the present application are easily hydrolyzed ions with a valence of divalence or above, which are conducive to the rapid formation of alkaline groups that combine with CO2, thereby improving the CO2 adsorption rate and adsorption capacity.
[0036] In some embodiments, the specific operation of step S2 is: adding the tertiary amine polymer solution dropwise to the cellulose dispersion, adding the crosslinking agent and stirring at 20-30° C., then adding the quaternary ammonium salt compound aqueous solution and stirring, and then performing a heat treatment at 40-80° C. and rinsing to obtain the modified cellulose.
[0037] In the present application, the reaction mechanism of step S2 is the Williamson etherification reaction mechanism. Taking epichlorohydrin as an example, its synthesis process is that the epoxy ring of the cross-linking agent is sensitive and reacts with cellulose to generate 3-chloro-2-hydroxy cellulose ether. Cellulose ether is rearranged by chloride ion replacement to generate a new epoxy ring, and attacks the nitrogen atom on the imidazole ring to generate a cross-linked copolymer. Among them, the temperature for adding the cross-linking agent and stirring the reaction is room temperature and the time is 0.5h. Under this temperature and time range, it is conducive to the formation of imidazole-cellulose cross-linked polymers; the temperature for adding the quaternary ammonium salt compound aqueous solution and stirring the reaction is room temperature and the time is 1-2h, and the temperature of the heat treatment is 40-80°C and the time is 1-3h; the purpose of the heat treatment is to promote the tertiary amine polymer and the quaternary ammonium salt to fully react with the cellulose, and realize the loading of multiple functional groups on the cellulose surface.
[0038] In some embodiments, the crosslinking agent includes one or more of epichlorohydrin, epibromohydrin, ethylene dichloride, and ethylene dibromide.
[0039] In some embodiments, the mass ratio of cellulose to the tertiary amine polymer is 1:(0.5-1.5); the mass ratio of cellulose to the quaternary ammonium salt compound is 1:(0.5-1.5).
[0040] In some embodiments, the alcohol used in step S3 includes one or more of methanol, ethanol, 2-methyl-2-propanol, and tert-butanol.
[0041] In a second aspect, the present application provides a humidity-responsive CO2 separation material.
[0042] In the third aspect, the present application provides an application of a humidity-responsive CO2 separation material in separating CO2 from the air, and the application steps include: placing the humidity-responsive CO2 separation material in a quartz tube to adsorb CO2 in a simulated air flow at 25°C and low humidity (RH≤60%); passing water-passed air through the saturated adsorption material and desorbing it at room temperature; and testing the cyclic adsorption capacity of the desorbed material after drying with hot air at 40-50°C.
[0043] The present solution is further described below through specific embodiments.
[0044] Example 1
[0045] A method for preparing a humidity-responsive CO2 separation material comprises the following steps:
[0046] S1. Disperse 1 g of cellulose in 50 ml of imidazolium chloride ionic liquid (1-butyl-3-methylimidazolium chloride, CAS79917-90-1) to obtain a transparent cellulose dispersion;
[0047] S2. 0.2 g of polyvinyl imidazole polymer (CAS 25232-42-2) was dissolved in 5 g of 25 wt% urea solution to obtain a tertiary amine polymer solution, the tertiary amine polymer solution was added dropwise to the cellulose dispersion and stirred at 25° C. to obtain a mixed solution, 0.1 g of epichlorohydrin was added to the mixed solution, stirred at 25° C. for 2 h, and 0.2 g of 3-chloro-2-hydroxypropylammonium chloride aqueous solution was added and stirred at 25° C. for 2 h to obtain a mixture, the mixture was placed in an oven at 60° C. for heat treatment for 1 h to obtain a solid substance, and the solid substance was rinsed with pure water until neutral to obtain modified cellulose;
[0048] S3. Soak the modified cellulose in 0.2 mol / L sodium phosphate solution for 6 hours, take it out, and repeat the soaking process 5 times. Rinse it with tert-butanol and freeze-dry it to obtain a humidity-responsive CO2 separation material.
[0049] Example 2
[0050] A method for preparing a humidity-responsive CO2 separation material comprises the following steps:
[0051] S1. Disperse 1 g of cellulose in 50 ml of sodium hydroxide / urea solution to obtain a cellulose solution;
[0052] S2. 0.2 g of polyvinylpyridine polymer (CAS: 25232-41-1) was dissolved in 5 g of 25 wt% urea solution to obtain a tertiary amine polymer solution, the tertiary amine polymer solution was added dropwise to the cellulose dispersion and stirred at 25°C to obtain a mixed solution, 0.1 g of epichlorohydrin was added to the mixed solution, stirred at 25°C for 2 h, and 0.2 g of (3-chloro-2-hydroxypropyl) dodecyldimethylammonium chloride aqueous solution was added and stirred at 25°C for 2 h to obtain a mixture, the mixture was placed in an oven at 40°C for heat treatment for 1 h to obtain a solid substance, and the solid substance was rinsed with pure water until neutral to obtain modified cellulose;
[0053] S3. Soak the modified cellulose in a 0.2 mol / L sodium borate solution for 6 hours, take it out, and repeat the soaking process 5 times. Rinse it with tert-butanol and freeze-dry it to obtain a humidity-responsive CO2 separation material.
[0054] Example 3
[0055] A method for preparing a humidity-responsive CO2 separation material comprises the following steps:
[0056] S1. Dispersing 1 g of cellulose in 50 ml of imidazolium chloride ionic liquid to obtain a cellulose dispersion;
[0057] S2. 0.2 g of polyvinyl imidazole polymer was dissolved in 5 g of 25 wt% urea solution to obtain a tertiary amine polymer solution, the tertiary amine polymer solution was added dropwise to the cellulose dispersion and stirred at 25° C. to obtain a mixed solution, 0.1 g of ethylene dichloride was added to the mixed solution, stirred at 25° C. for 2 h, and 0.2 g of 2,3-epoxypropyltrimethylammonium chloride aqueous solution was added and stirred at 25° C. for 2 h to obtain a mixture, the mixture was placed in an oven at 80° C. for heat treatment for 1 h to obtain a solid substance, and the solid substance was rinsed with pure water until neutral to obtain modified cellulose;
[0058] S3. Soak the modified cellulose in a 0.2 mol / L sodium silicate solution for 6 hours, take it out, and repeat the soaking process 5 times. Rinse it with tert-butanol and freeze-dry it to obtain a humidity-responsive CO2 separation material.
[0059] Comparative Example 1
[0060] A method for preparing a humidity-responsive CO2 separation material, the other contents of which are the same as those of Example 1, except that the method does not include adding a tertiary amine polymer solution.
[0061] Comparative Example 2
[0062] A method for preparing a humidity-responsive CO2 separation material, the other contents of which are the same as those of Example 1, except that the addition of an aqueous solution of 3-chloro-2-hydroxypropylammonium chloride is not included.
[0063] Comparative Example 3
[0064] A method for preparing a humidity-responsive CO2 separation material, the other contents of which are the same as those of Example 1, except that neither a tertiary amine polymer solution nor an aqueous solution of 3-chloro-2-hydroxypropylammonium chloride is included.
[0065] Comparative Example 4
[0066] A method for preparing a humidity-responsive CO2 separation material, the other contents of which are the same as those of Example 1, except that the tertiary amine polymer solution is replaced by 2-methylimidazole.
[0067] Comparative Example 5
[0068] A method for preparing a humidity-responsive CO2 separation material, the other contents of which are the same as those of Example 1, except that the method does not include soaking in a sodium phosphate solution.
[0069] Comparative Example 6
[0070] A method for preparing a humidity-responsive CO2 separation material, the other contents of which are the same as those of Example 1, except that sodium phosphate is replaced by sodium carbonate.
[0071] Comparative Example 7
[0072] A method for preparing a humidity-responsive CO2 separation material, the other contents of which are the same as those of Example 1, except that freeze drying is replaced by vacuum drying.
[0073] Test and Evaluation
[0074] The humidity-responsive CO2 separation materials obtained in each embodiment and comparative example were tested for CO2 adsorption capacity, average adsorption rate (0.5h), desorption rate and cyclic adsorption capacity at different humidity. The results are shown in Table 1.
[0075] The test methods for each parameter are as follows: Place different humidity-responsive CO2 separation materials in a quartz tube and use them to adsorb CO2 in a simulated air flow at 25°C and humidity (RH=30%, RH=45%, RH=60%). After adsorption saturation, the material is passed through water-saturated air and desorbed at room temperature. After the desorbed material is dried with 40-50°C hot air, the cyclic adsorption capacity can be tested.
[0076] Table 1 Test results
[0077]
[0078] As can be seen from Table 1, the adsorption capacity and adsorption rate of adsorbent are all higher in Examples 1-3, especially, under RH of 60%, higher adsorption capacity is also maintained, indicating that the synergistic effect of cellulose material porous structure and surface functional groups prompts the material to have higher adsorption performance. In Comparative Example 1, tertiary amine polymer is not added to make the adsorption capacity decline, but the quaternary ammonium salt functional group makes its adsorption rate faster because of the small steric hindrance. In Comparative Example 2, quaternary ammonium salt functional group is not added to make the adsorption capacity and adsorption rate decline. In Comparative Example 3, without adding any functional group modification, cellulose is to CO2 adsorption capacity and adsorption rate are all lower, and it can be seen from the data of Example 1 and Comparative Examples 1-3 that along with the increase of humidity, the synergistic effect of tertiary amine polymer and quaternary ammonium salt functional group is more obvious. In Comparative Example 4, 2-methylimidazole is adopted to replace tertiary amine polymer, and the fiber surface is all imidazolium salt and quaternary ammonium salt functional group, and adsorption capacity and adsorption rate do not have obvious change. However, under high humidity conditions, the adsorption capacity and rate of the material drop sharply. Although imidazolium salts have high adsorption selectivity, high humidity environmental conditions make it difficult for imidazolium salts to exert their adsorption selectivity. The simultaneous introduction of tertiary amine functional groups into cellulose materials can significantly improve the adsorption performance under high humidity. In Comparative Example 5, the material that has not undergone ion exchange reaction lacks basic groups and is difficult to adsorb CO2. In Comparative Example 6, carbonate is used instead of phosphate. Due to the slow hydrolysis rate of carbonate, the rate at which the material adsorbs CO2 becomes slower. In Example 7, vacuum drying is used instead of freeze drying. Due to the partial collapse of the pore structure of the material obtained by vacuum drying, the adsorption capacity and adsorption rate of the material are reduced.
[0079] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a humidity-responsive CO2 separation material, characterized in that: The following steps are involved: S1. dispersing cellulose in a good solvent system to destroy hydrogen bonds to obtain a cellulose solution; S2. The tertiary amine polymer solution is added dropwise to the cellulose solution, a crosslinking agent is added for Williamson etherification reaction, and then an aqueous solution of a quaternary ammonium salt compound is added and stirred for reaction, and then heat treated and rinsed to obtain modified cellulose; S3. The modified cellulose is immersed in a solution of a strong base and a weak acid salt to carry out ion exchange, and then the solution is rinsed with alcohol and freeze-dried to obtain a humidity-responsive CO2 separation material; the strong base and a weak acid salt contains a trivalent anion; the tertiary amine polymer includes polyvinyl imidazole; the quaternary ammonium salt compound includes one or more of 3-chloro-2-hydroxypropylammonium chloride, (3-chloro-2-hydroxypropyl) dodecyldimethylammonium chloride, and 2,3-epoxypropyltrimethylammonium chloride; the strong base and a weak acid salt includes one or more of sodium phosphate and sodium dihydrogen phosphate.
2. The method for preparing a humidity-responsive CO2 separation material according to claim 1, characterized in that: The good solvent includes one or more of imidazolium chloride ionic liquid and sodium hydroxide / urea mixed solution; the cellulose is type I cellulose, which has a double-chain alternating structure and a crystal density of (1.59-1.61) g cm -3 , the viscosity average molecular weight is (10-20)×10 4 .
3. The method for preparing a humidity-responsive CO2 separation material according to claim 1, characterized in that: In step S2, the heat treatment temperature is 40-80°C.
4. The method for preparing a humidity-responsive CO2 separation material according to claim 1, characterized in that: The cross-linking agent includes one or more of epichlorohydrin, epibromohydrin, ethylene dichloride and ethylene dibromide.
5. The method for preparing a humidity-responsive CO2 separation material according to claim 1, characterized in that: The mass ratio of the cellulose to the tertiary amine polymer is 1: (0.5-1.5).
6. A humidity-responsive CO2 separation material obtained by the preparation method according to any one of claims 1 to 5, characterized in that: The invention comprises cellulose and a tertiary amine group, a quaternary ammonium salt group and an imidazolium salt group supported on the cellulose.
7. Use of the humidity-responsive CO2 separation material as claimed in claim 6 in separating CO2 from air, characterized in that: Air humidity ≤60%.
Citation Information
Patent Citations
Preparation method of resin-based carbon dioxide adsorbent
CN108043368A
Preparation method and application of cellulose-based porous material for carbon capture
CN115845810A
Quaternary ammonium group modified polyurethane CO2 adsorbent and preparation method thereof
CN117339571A